Between Cultural Essence and Stereotype. A Visual Analysis of Childish Gambino’s “This is America” - Mondillo, Mirko; de Majo, Claudio (SigMa - Rivista di Letterature comparate, Teatro e Arti dello spettacolo, 2021)
Focusing our attention on its setting, its choreographic choices, the protagonist’s gestures, the stage costumes and through the lenses of visual and communication, we develop a critical analysis illustrating the political and social discourses provided by This Is America. As the song’s lyrics do not explicitly deal with topics such as gun control, police brutality and racism, this essay focuses on visual theory in order to assess the emergence of these themes along the visual images of the videoclip. In this sense, this research effort focuses on two main critical aspects: on the one hand, it assesses the visual strategies adopted by Gambino and Murai in order to produce a critical discourse on race relations in America without falling into the usual clichés associated to Black culture. On the other hand, it looks at the multiple cultural references to black culture, from pop music to the cinematic production of Spike Lee and Jordan Peele, and how these are weaved into the video clip of This is America, though the adoption of inflated images, allegories, metaphors and symbols. In this essay, we provide a visual analysis of Childish Gambino video clip This is America, directed by Hiro Murai in 2018. We attempt to understand the multiple interpretative layers and contents of Gambino’s video and song.